Academic and Media Narratives on Russia’s War Against Ukraine - Ярошенко, О. (Київський національний університет імені Тараса Шевченка, 2025)
Modern Challenges of Journalism Highlight the Need for Effective Work with Various Information Sources, Including Scientific Publications and Research Data. These sources can serve as key tools for journalists, contributing to the objective coverage of events. The main objective of the study is to explore the role of journalism as a crucial instrument in shaping media discourse in the context of the Russia-Ukraine war, particularly by analyzing manipulations with scientific publications and the processes of the mediatization of science. Methodology. To achieve this goal, content analysis, discourse analysis, generalization, and systematization methods were applied. Content analysis allowed for the examination of academic texts, while discourse analysis of news texts helped identify potential manipulations in the presentation of scientific information in the media. Results and conclusions. The study’s findings demonstrate that, to ensure objective event coverage, journalists must carefully evaluate scientific research and expert opinions, focusing on the comprehensive representation of scientific results rather than isolated fragments. This will contribute to the more ethical and responsible use of scientific data in the media.

Сучасні виклики журналістської діяльності підкреслюють необхідність вміти ефективно працювати з різними джерелами інформації, включаючи наукові публікації та дослідницькі дані. Ці джерела здатні слугувати ключовим інструментом для журналістів, сприяючи об’єктивному висвітленню подій. Мета статті – визначити роль журналістики як важливого інструменту формування медіадискурсу в контексті російсько-української війни. Для цього проаналізовано маніпуляції з науковими публікаціями та процеси медіатизації науки. Для досягнення поставленої мети були застосовані методи контент-аналізу, дискурс-аналізу, узагальнення та систематизації. Контент-аналіз дав змогу дослідити академічні тексти, а дискурс-аналіз текстів новин допоміг виявити потенційні маніпуляції в подачі наукової інформації в медіа. Результати дослідження демонструють, що для забезпечення об’єктивного висвітлення подій журналістам необхідно ретельно оцінювати наукові дослідження та експертну думку, зосереджуючись на цілісному відображенні наукових результатів, а не на окремих фрагментах. Це сприятиме більш етичному та відповідальному використанню наукових даних у медіа.
Академічні та медійні наративи про війну Росії проти України
Keywords: Russia-Ukraine War; academic discourse; media discourse; information warfare; hybrid war; media; mediatization of science; media and science; journalism ethics; російсько-українська війна; академічний дискурс; медійний дискурс; інформаційна війна; гібридна війна; медіа; медіатизація науки; медіа та наука; журналістська етика